Implementasi Prinsip Pariwisata Berkelanjutan dalam Pengelolaan Destinasi Wisata Pesisir - Ahmad Ramadhan; Siti Maharani (Lembaga Penelitian dan Pendidikan, 2025)
Coastal tourism destinations have significant economic potential but are also vulnerable to environmental degradation if not managed sustainably. This study explores the implementation of sustainable tourism principles in the management of coastal tourism areas. The purpose is to identify effective strategies that balance environmental conservation, community involvement, and economic development. A qualitative descriptive method was employed, with data collected through field observations, semi-structured interviews with local stakeholders, and literature analysis. The findings reveal that sustainable management practices, such as waste management, zoning systems, community empowerment programs, and eco-friendly infrastructure, have a positive impact on both environmental quality and local livelihoods. However, challenges remain in terms of policy enforcement, limited stakeholder coordination, and lack of environmental awareness among visitors. This study concludes that sustainable coastal tourism management requires strong collaboration between government, local communities, and private sectors, supported by continuous education and monitoring programs. The results provide practical implications for policymakers and destination managers to design long-term strategies that ensure both environmental sustainability and community welfare.